WAYS OF WORDFORMATION. STRUCTURAL PECULIARITIES OF LEXICON (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the multifaceted world of word formation and the structural peculiarities that govern the lexicon of a language. Through a well-structured exploration, it elucidates the diverse processes involved in creating and modifying words, highlighting derivation, compounding, blending, clipping, acronym formation, and more. Each of these mechanisms is elucidated with clear examples, making the intricate world of linguistic evolution accessible to readers. Furthermore, the article adeptly navigates the structural peculiarities of lexicon, emphasizing its complex web of semantic fields, morphological and syntactic patterns, as well as the presence of lexical gaps and neologisms. By illustrating how words are interconnected within semantic fields and shaped by morphological and syntactic rules, it provides a profound understanding of the organization and evolution of language.